2016
DOI: 10.1038/srep32388
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Doppler Effects in Broadband Acoustic Metamaterials

Abstract: The Doppler effect refers to the change in frequency of a wave source as a consequence of the relative motion between the source and an observer. Veselago theoretically predicted that materials with negative refractions can induce inverse Doppler effects. With the development of metamaterials, inverse Doppler effects have been extensively investigated. However, the ideal material parameters prescribed by these metamaterial design approaches are complex and also challenging to obtain experimentally. Here, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…The abnormal Doppler phenomenon was tested with a moving sound source. In 2015, Zhai et al [71] designed an acoustic metamaterial with seven A lot of research has been done on the negative refraction effect of phononic crystals. Yang et al [67] studied a phononic focusing phenomenon in the passband over a complete band gap in a 3D phononic crystal and found that the wave propagation depends largely on the frequency and the direction of incidence, and due to the anisotropy of the propagation, very large negative refraction occurs.…”
Section: Anomalous Doppler Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…The abnormal Doppler phenomenon was tested with a moving sound source. In 2015, Zhai et al [71] designed an acoustic metamaterial with seven A lot of research has been done on the negative refraction effect of phononic crystals. Yang et al [67] studied a phononic focusing phenomenon in the passband over a complete band gap in a 3D phononic crystal and found that the wave propagation depends largely on the frequency and the direction of incidence, and due to the anisotropy of the propagation, very large negative refraction occurs.…”
Section: Anomalous Doppler Effectmentioning
confidence: 99%
“…The abnormal Doppler phenomenon was tested with a moving sound source. In 2015, Zhai et al [71] designed an acoustic metamaterial with seven flute-like binary molecular clusters. Their research found that this metamaterial has both local elastic modulus and local density of mass density, and can achieve negative refraction over a wide frequency range, and also exhibit broadband reverse Doppler effect.…”
Section: Anomalous Doppler Effectmentioning
confidence: 99%
“…Local resonance band gaps are based on resonant structures with subwavelength sizes less than λ/3. Furthermore, some other kinds of passively and actively tunable AMMs have been presented to study the broadband AMMs [45,46,47,48]. All the methods to realize broadband AMMs are based on the intrinsic properties of the unit cells.…”
Section: Introductionmentioning
confidence: 99%
“…The rising acoustic metamaterials, whose structures are on a subwavelength scale, exhibit many novel properties that can not be realized by natural materials in controlling sound waves, such as negative mass density, negative modulus, and double-negative parameters [1][2][3][4][5][6][7][8][9][10]. Liu et al embedded rubber-coated lead spheres into epoxy matrix and first realized a metamaterial with negative effective mass density [1].…”
Section: Introductionmentioning
confidence: 99%